Confidence level and knowledge of pre-hospital thrombolysis therapy of paramedic in pre-hospital care: a survey - Nik Azlan Nik Muhamad; Muhamad Syis Z (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
Data on knowledge, attitude and ST Elevation Myocardial Infarction (STEMI) electrocardiography (ECG) detection among pre-hospital paramedics in Malaysia is still scarce. It is imperative to gain this information as a pre-requisite in initiating pre-hospital thrombolysis. This was a descriptive study conducted from May 2016 until November 2017 on paramedics from Universiti Kebangsaan Malaysia Medical Center (UKMMC) and Kuala Lumpur Hospital (HKL). It was to assess knowledge on pre-hospital thrombolytic therapy and ECG detection of STEMI. One hundred and six questionnaires were answered and analyzed. More than 60% of the candidates were unable to detect STEMI ECG changes and lacked of confidence in handling and administering thrombolytic treatment at the level of pre-hospital phase. Only 20.8% candidates managed to detect more than 8/10 of the correct ECG pattern in STEMI. Less than 40% of the candidates achieved more than 80% marks in answering questions regarding STEMI and treatment. It is concluded that the overall performance and knowledge of paramedic regarding pre-hospital thrombolytic therapy is generally poor. Further training need to be done prior to implementing pre-hospital STEMI thrombolytic therapy in Malaysia.